MATHEMATICAL LEARNING REVEALED THROUGH TABLET SCREEN TOUCH WHEN MANIPULATING THE MULTIBASE APPLICATION - Rony Freitas; Marcelo Almeida Bairral (Universidade do Estado do Rio de Janeiro (UERJ), 2023)
Introducing the notion of quantity and mathematical operations in the early years of schooling has been a challenge for teachers. When the tablet becomes part of the activities, this challenge increases. This article aims to illustrate a mapping of screen touches and indicate their purposes in an activity, involving addition and subtraction operations, performed with the aid of the Multibase application. The data were produced through filmed records, screen recordings from Multibase using the Screen Recorder application, activities and records made by the students themselves. The analysis sought to: 1) map and illustrate screen touches performed in Multibase; and 2) identify the purpose of these touches. The groupings were done by touching objects contour movements, the organization of objects by dragging touches and the counting in pointing touches. The study contributes to inclusion and technological innovation by showing Multibase in a digital version and highlighting other forms of communication and language that can be inserted in different teaching programs.